2015
DOI: 10.1016/j.asjsur.2012.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic perivascular epithelioid cell tumor: Five case reports and literature review

Abstract: Perivascular epithelioid cell tumor (PEComa) is a rare tumor. Here, we present data regarding clinical presentations, diagnoses, management, and prognosis of five cases of hepatic PEComa between January 2002 and December 2008. Ultrasonography showed hyperechoic masses in all patients. Precontrast computed tomography (CT) showed that all lesions scanned were heterogeneous in density and were heterogeneously enhanced in arterial phase images. In two cases, magnetic resonance imaging showed hypointensity on T1-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 29 publications
3
34
1
1
Order By: Relevance
“…A PEComa can occur in many parts of the human body, such as the uterus, skin, thorax, gastrointestinal tract and liver. The prognosis of benign hepatic PEComas, which are able to be radically cured by surgery, is usually satisfactory and little evidence of recurrence or metastasis of these tumours has been reported after surgery in previous case studies [1][2][3][4][5][6][7][8][9][10][11]. In contrast, malignant hepatic PEComas characterized by aggressive growth and early metastasis have a poor prognosis, but the incidence is much lower than benign hepatic PEComas [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A PEComa can occur in many parts of the human body, such as the uterus, skin, thorax, gastrointestinal tract and liver. The prognosis of benign hepatic PEComas, which are able to be radically cured by surgery, is usually satisfactory and little evidence of recurrence or metastasis of these tumours has been reported after surgery in previous case studies [1][2][3][4][5][6][7][8][9][10][11]. In contrast, malignant hepatic PEComas characterized by aggressive growth and early metastasis have a poor prognosis, but the incidence is much lower than benign hepatic PEComas [12].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, malignant hepatic PEComas characterized by aggressive growth and early metastasis have a poor prognosis, but the incidence is much lower than benign hepatic PEComas [12]. Studies have con rmed that 6-10% of cases of hepatic PEComa are associated with a genetic disease called TSC, because the pathogenesis of PEComa may be related to the deletion of TSC1 (9q34) or TSC2 (16p13.3) [2]. Shih-Chiang Huang et al [13], who had analysed specimens of hepatic PEComa, also found that hepatic PEComas are associated with an alteration in the mTOR pathway and a loss of heterozygosity (LOH) in the TSC1/TSC2 genes, particularly in TSC2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This type of tumor consists of three components: thick-walled often hyalinized blood vessels, smooth muscle cells, and adipose tissue. Angiomyolipoma of the kidney and liver, clear cell “sugar” tumor of the lung, and lymphangiomyomatosis are all PEComas (7). There have been approximately 100 cases of PEComas previously reported in the literature, either as case reports or small sample studies.…”
Section: Discussionmentioning
confidence: 99%